KAJIAN KEARIFAN LOKAL BUDAYA MELAYU DI DESA PANGKALAN BUTON, KECAMATAN SUKADANA, KABUPATEN KAYONG UTARA - Irawan Setyabudi; Ade Rohan; Wahidyanti Rahayu Hastutiningtyas (Universitas Tribhuwana Tunggadewi, 2019)
Human understanding of nature and forms of human behavior due to its closeness to cultural elements, shape the local wisdom of the community. Cultural values, attitudes, and behaviors that are culturally oriented in the life structure of local communities shape the cultural intelligence of a community, which is formed in the existing traditional rituals. Customary rituals have different meanings and procedures in each region, specifically in Pangkalan Buton Village, Sukadana Subdistrict, the surrounding community interprets it as a tribute to their ancestors or ancestors as a form of gratitude. Based on observations made by researchers, there are several traditional rituals such as the tradition of Nyambut Tamu, Tepung Tawa, Betangas, and Mandi Safar. The problem is the tradition is rarely seen because of the rapid progress of the times, making the behavior or knowledge of an object that is Malay culture increasingly fade, especially among teenagers. The purpose of this study was to identify the local wisdom of Malay culture through several traditional rituals in the village of Pangkalan Buton. This research method is a qualitative study, using the Focus Group Discussion (FGD) method as a data processing tool that has been collected previously in the traditional rituals of Nyambut Tamu in the village of Buton base. The stages of the research began from the identification of problems, permits, observational studies in the form of data collection and interviews to the process of analysis-synthesis associated with the Malay cultural traditions. The results of the study were in the form of descriptions of various forms of local community cultural traditions, especially in the residents of Pangkalan Buton village, Sukadana District, Kayong Utara Regency. The study concludes that each region in the archipelago has a unique tradition that is different and needs to be preserved, with the results of this identification will bring up a 'sense of belonging' for local residents.